The teacher of physical education and emotional intelligence - Margarita Gutiérrez Moret; Raquel Ibáñez Martínez (INFAD, 2017)
The subject of physical education has characteristics that make it suitable for the development of management skills and emotional regulation in students. But the emotional intelligence that is developing in physical education classrooms must have as a previous step the training of teachers in these emotional skills. This paper presents the results of the analysis on the emotional profile of future physical education teachers through a measure of self-perception in Emotional Intelligence.